A perspective on the structure and receptor-binding properties of immunoglobulin G Fc - Hanson, Quinlin M. (Biochemistry, 2015)
Recombinant antibodies spurred a revolution in medicine that saw the introduction of powerful therapeutics for treating a wide range of diseases, from cancers to autoimmune disorders and transplant rejection with more applications looming on the horizon. Many of these therapeutic monoclonal antibodies (mAbs) are based on human immunoglobulin G1 (IgG1), or at least contain a portion of the molecule. Most mAbs require interactions with cell surface receptors for efficacy, including the Fc γ receptors (FcγRs). High-resolution structural models of antibodies and antibody fragments have been available for nearly forty years, however, a thorough description of the structural features that determine the affinity with which antibodies interact with human receptors is not known. In this review we will cover the relevant history of IgG-related literature and how recent developments have changed our view of critical antibody-cell interactions at the atomic level with a nod to outstanding questions in the field and future prospects.